Clinical characteristics of fatalities due to influenza A (H1N1) virus in Mexico. Issue 6 (3rd June 2010) - Fajardo-Dolci, Germán; Gutierrez-Vega, Rafael; Arboleya-Casanova, Heberto; Villalobos, Aremis; Wilson, Kate S; García, Sandra G; Sotelo, Julio; Córdova Villalobos, José A; Díaz-Olavarrieta, Claudia
Abstract : Background: Mexico has experienced a disproportionate mortality burden due to the influenza A(HIN1) pandemic. A study was undertaken to investigate the sociodemographic and clinical characteristics of the first 100 patients who died from confirmed influenza A(H1N1). Methods: A clinical evaluation was made of the first 100 consecutive deaths of confirmed cases between 10 April and 28 May 2009 reported by the Federal Ministry of Health. Statistical analysis included disease frequencies and descriptive comparisons with national health data. Results: Most patients (60%) were aged 30–79 years, 53% were female and 40% were residents of Mexico City. On admission, 50% had one or more chronic medical conditions including metabolic syndrome (40%), cardiovascular disease (21%), diabetes (20%), hypertension (20%) and respiratory disease (8%). 38% of women and 26% of men were obese based on body mass index). The main clinical symptoms were fever (84%), cough (85%), dyspnoea (75%) and myalgia (30%). The frequency of all chronic diseases was higher in this sample than in the national statistics. Most (82%) developed symptoms before the Mexican government issued the influenza alert (24 April). Median hospital stay prior to death was 4 days (range 0–58). Conclusions: Patients, mostly young adults, who died from A(HIN1) influenza had a high frequency of one or more chronic diseases upon admission. Most died shortly after the health authorities initiated national influenza control measures.